Analisis Pola Komunikasi Melalui Media Sosial untuk Mendukung Pemasaran Produk ATK: Studi Kasus 5 Produsen Alat Tulis di Indonesia - Andri Kurniawan; Rini Sudarmanti; Dwi Purbaningrum; Titis Gandariani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Currently, digital developments encourage all business actors, both large, medium, small, and MSMEs, to intensively use social media as part of an integrated marketing communications strategy (integrated marketing communications). Except for office stationery (ATK) manufacturers in Indonesia, who are focused on working on the stationery market in the midst of the era of digitalization, as well as the threat of products from China and the addition of intense domestic competition, resulting in the rise of counterfeit products in this sector. This research aims to analyze in more depth digital communication patterns through the use of social media from stationery manufacturers using qualitative research methods with comparative case studies. The research was conducted over a period of 14 days, in 1-14 June 2024, by looking at patterns and comparisons of digital communication on the Instagram platform from 5 stationery manufacturers in Indonesia who have used social media optimally, especially ahead of the New Academic Year. The research results show that 5 stationery manufacturers in Indonesia have used social media as a communication channel to the public in order to improve brand image and increase brand awareness, but this needs to be improved in several ways in the future.